2014
DOI: 10.1096/fj.14-261636
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with thrombospondin‐1 type I repeats (3TSR) and chemotherapy induces regression and significandy improves survival in a preclinical model of advanced stage epithelial ovarian cancer

Abstract: Most women are diagnosed with epithelial ovarian cancer (EOC) at advanced stage, where therapies have limited effectiveness and the long-term survival rate is low. We evaluated the effects of combined antiangiogenic and chemotherapy treatments on advanced stage EOC. Treatment of EOC cells with a recombinant version of the thrombospondin-1 type I repeats (3TSR) induced more apoptotic cell death (36.5 6 9.6%) in vitro compared to untreated controls (4.1 6 1.4). In vivo, tumors were induced in an orthotopic, syng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 53 publications
(83 reference statements)
3
67
0
Order By: Relevance
“…It is known that adhesion is a necessary factor for spheroid formation, and studies have suggested that free cells detached from the primary tumor may form spheroids through the interaction between α 5 β 1 integrin and fibronec- Cell culture. The ID8 (mouse EOC line) was a gift from Jack Lawler and Carmelo Nucera at Beth Israel Deaconess Medical Center (Harvard Medical School, Boston, Massachusetts, USA) (49). SKOV3 cells (human ovarian adenocarcinoma cell line) were obtained from ATCC.…”
Section: 0mentioning
confidence: 99%
“…It is known that adhesion is a necessary factor for spheroid formation, and studies have suggested that free cells detached from the primary tumor may form spheroids through the interaction between α 5 β 1 integrin and fibronec- Cell culture. The ID8 (mouse EOC line) was a gift from Jack Lawler and Carmelo Nucera at Beth Israel Deaconess Medical Center (Harvard Medical School, Boston, Massachusetts, USA) (49). SKOV3 cells (human ovarian adenocarcinoma cell line) were obtained from ATCC.…”
Section: 0mentioning
confidence: 99%
“…The ID8 (mouse epithelial OC line) was gifted from Jack Lawler and Carmelo Nucera at Beth Israel Deaconess Medical Center, Harvard Medical School (47). SKOV3 (human ovarian adenocarcinoma cell line) were obtained from ATCC.…”
Section: Administration Of Ask1 Inhibitor (Ask1i) Gs444217 In Micementioning
confidence: 99%
“…Attachment to sulfated glycans of cell surfaces and extracellular matrix has been observed for mammalian and Plasmodium proteins (5)(6)(7). In addition, the three TSRs of thrombospondin-1 have been shown to interact with the cell surface receptor CD36 with resultant antiangiogenic effects (8) and are being explored as an anticancer therapy (9).…”
mentioning
confidence: 99%